A mechanical instrument to evaluate posture of the spinal column in pregnant women - Secca, Mario (2013)
Back pain is a very important problem in modern society. To better understand this problem we need instruments that evaluate the spinal column in a global way. There are many instruments used to evaluate the spinal column, like X-rays, Computed Tomography scans and Magnetic Resonance Imaging. However very few of them are radiation safe and permit the analysis of the spinal column in a vertical standing position and they tend to evaluate only parts of this osseous structure, like the flexible ruler or the "Metrecom Skeletal Analysis System". We want to study the evolution of posture in women during pregnancy and require a completely safe instrument to give the change of all the vertebrae locations throughout time. We built a fully mechanical system, which we called Vertebral Metrics, with the objective of evaluating the curvatures and lateral deviations of the spinal column in the standing position. It is a non-invasive instrument that was originally planned and built to be used with pregnant women that cannot be subjected to any radiation, but which can be used for any type of population. The instrument is composed of two parts: a measuring part, which is the body of the instrument, and a supporting part, which is where the measuring part is fixed. The measuring part consists of 17 identical adjustable mechanical blocks that allow us to reproduce the position of each vertebra of the spinal column, from the first cervical vertebra, to the first sacral vertebra. Since it is a completely mechanical instrument it can be used anywhere and could easily be used anywhere in the world without the use of electricity.